Design of crescent slot circularly polarised patch for 4G wireless communications. (2019) - Saravanan, Manavalan; Rangachar, Madihally Janardhana Srinivasa
A single fed circularly polarised patch antenna operating at 4G long term evolution (LTE) is proposed. The antenna is excited by means of 50 Ω coaxial cable placed near to edge of the patch element. In order to achieve circular polarisation, a crescent-shaped slot is incorporated in the radiating element which perturbs the surface current fields on the radiating patch element. Based on the slot orientation, the antenna radiates either left-hand or right-hand polarisation. The shape of the crescent slot and position of feed point are tuned to improve 3db axial ratio beam width of the antenna. The antenna parameters are characterised using Ansoft high frequency structure simulator and further, parametric analysis on antenna dimensions are carried and its effects on antenna performance are discussed. The antenna attains −10 dB impedance bandwidth (2.55 GHz to 2.6 GHz) in the 4G band and achieves a return loss of −16.06 dB with a peak gain of 5.94 dB at its operating frequency. The antenna also achieves wider axial ratio (AR) beam width of 105 0 (AR ≤ −3 dB) and good cross-polarisation isolation of −17.93 dB which makes it more suitable for modern wireless communications.